2017
DOI: 10.1080/10810730.2016.1275890
|View full text |Cite
|
Sign up to set email alerts
|

Using Community Engagement to Develop a Web-Based Intervention for Latinos about the HPV Vaccine

Abstract: Human papillomavirus (HPV) infection is pervasive among sexually active women and men, and Hispanic women are at particularly high risk as they have higher rates of invasive cervical cancer compared to other racial or ethnic groups in the United States. There is a need for interventions to increase HPV vaccination among this high-risk population. This study investigated how to modify a previously developed web-based intervention that provided individually tailored information about HPV to improve its use among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…The majority of parents (83.3%) participating in this study reported having heard of the HPV vaccine from their child's physician. This important finding adds to research evidence that indicates the central role physician's play in increasing parents' awareness of the HPV vaccine, and ultimately in influencing the uptake of the HPV vaccine for their adolescent children [52][53][54]. Nonetheless, in agreement with prior studies conducted among Latino parents [21,26,28,29] and other racial/ethnic minorities [18,[38][39][40][41], findings of the present study also determined that fewer fathers reported hearing about the HPV vaccine from their child's physician than mothers.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of parents (83.3%) participating in this study reported having heard of the HPV vaccine from their child's physician. This important finding adds to research evidence that indicates the central role physician's play in increasing parents' awareness of the HPV vaccine, and ultimately in influencing the uptake of the HPV vaccine for their adolescent children [52][53][54]. Nonetheless, in agreement with prior studies conducted among Latino parents [21,26,28,29] and other racial/ethnic minorities [18,[38][39][40][41], findings of the present study also determined that fewer fathers reported hearing about the HPV vaccine from their child's physician than mothers.…”
Section: Discussionsupporting
confidence: 89%
“…80,81 Researchers have worked with communities to design web-based interventions and social media tools to address parental concerns about early childhood and adolescent vaccines. 82,83 Some studies have shown success in the use of text messaging, web-based patient portals, and online promotion of immunization campaigns; however, there is still a paucity of evidence on use of social media. 84 Online media may prove useful both for communication about vaccines and in monitoring hesitancy.…”
Section: Electronic Interventionsmentioning
confidence: 99%
“…Traditional methods for determining program requirements have usually involved focus groups or interviews [15]. The end user becomes a consultant who responds to the researcher’s predefined questions [13].…”
Section: Introductionmentioning
confidence: 99%